Pengaruh Penggunaan Media Video Animasi Terhadap Kemampuan Menyimak Cerita Dongeng Pada Siswa Kelas III Sekolah Dasar - M. Juanparestu; Susanti Faipri Selegi; David Budi Irawan (Journal of Practice Learning and Educational Development, 2025)
This study aims to determine the effect of using animated video media on the ability to listen to fairy tales in grade III students of SDN 10 Pemulutan. The study used a quantitative approach with a pre-experimental design of one group pre-test and post-test design. The subjects in this study were 30 grade III students. The instrument used was a listening ability test given before and after treatment. Data analysis was carried out using a paired sample t-test. The results showed that there was a significant effect of using animated video media on improving students' listening skills. This is indicated by a significance value of 0.034 (p <0.05), as well as an increase in the average value from the pre-test of 64.53 to 75.20 in the post-test. Thus, it can be concluded that animated video media is effective in improving the ability to listen to fairy tales in grade III students of SDN 10 Pemulutan, South Sumatra.